Syndicate marriage or tafficking? The travails of Asian migrant women - Md Said, Muhamad Helmi; Kaka, Grace Emmanuel; Drs Nasrul, Muhammad Amrullah; Cahyan, Tinuk Dwi (Ritchmann Publishing, 2022)
Migration is a phenomenon that has come to stay. It cuts across all nations in the world. People migrate for different purposes such as education, marriage, labour, job opportunity or employment and shelter for refugees. Migration occurs through various mediums which could be self, family members, friends, or other intermediaries such as brokers. This research applied the pure library-based research method to highlight the activities of brokers in migration in Asia and examine the ordeals of women victims in cross-border migration. It was discovered that activities of these illegal brokers, that is also known as syndicates, are not different from human trafficking. The women victims, whose desires are to change their status, soon got trapped in uncertainty with shattered dreams, hence the suggestion that Asian countries enter into bilateral agreement to enable favourable and a less strict migration procedures for their member states. In addition, the contracting states should enact strict legislation to curb syndicate marriage and check the accesses of these illegal brokers.